Partners in crime: proteins implicated in RNA repeat expansion diseases - Baud, Anna; Derbis, Magdalena; Tutak, Katarzyna; Sobczak, Krzysztof (Wiley, 2022)
Short tandem repeats are repetitive nucleotide sequences robustly distributed in the human genome. Their expansion underlies the pathogenesis of multiple neurological disorders, including Huntington's disease, amyotrophic lateral sclerosis, and frontotemporal dementia, fragile X-associated tremor/ ataxia syndrome, and myotonic dystrophies, known as repeat expansion disorders (REDs). Several molecular pathomechanisms associated with toxic RNA containing expanded repeats (RNAexp) are shared among REDs and contribute to disease progression, however, detailed mechanistic insight into those processes is limited. To deepen our understanding of the interplay between toxic RNAexp molecules and multiple protein partners, in this review, we discuss the roles of selected RNA-binding proteins (RBPs) that interact with RNAexp and thus act as “partners in crime” in the progression of REDs. We gather current findings concerning RBPs involved at different stages of the RNAexp life cycle, such as transcription, splicing, transport, and AUG-independent translation of expanded repeats. We argue that the activity of selected RBPs can be unique or common among REDs depending on the expanded repeat type. We also present proteins that are functionally depleted due to sequestration on RNAexp within nuclear foci and those which participate in RNAexp-dependent innate immunity activation.
Keywords: liquid–liquid phase separation; RAN translation; repeat expansion; RNA binding proteins; short tandem repeats